2010
DOI: 10.1111/j.1750-2659.2010.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of influenza-vaccinated health care workers toward masks to prevent nosocomial transmission of influenza

Abstract: Please cite this paper as: Brandt et al. (2010) Attitudes of influenza‐vaccinated health care workers toward masks to prevent nosocomial transmission of influenza. . Influenza and Other Respiratory Viruses 5(1), 61–66. Background  Influenza viruses are highly contagious. Health care workers (HCWs) are at risk of occupational exposure to influenza and may transmit the infection to their patients and coworkers. Objectives  The aim of the study was to characterize the attitudes of HCWs regarding the use of surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Since risk perception of vaccination rates is higher in pandemics periods, Sevencan et al found the rates 36.4% whereas Ormen et al detected the rates up to 40.0% [13,14]. The reason for lower rates of vaccination in similar studies conducted worldwide is similar to the reasons detected in our country [15,16,17]. The most common reasons for rejection of the vaccination include being afraid of side effects of the vaccine, not believing the effectiveness of the vaccine and not considering the vaccine safe [18].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Since risk perception of vaccination rates is higher in pandemics periods, Sevencan et al found the rates 36.4% whereas Ormen et al detected the rates up to 40.0% [13,14]. The reason for lower rates of vaccination in similar studies conducted worldwide is similar to the reasons detected in our country [15,16,17]. The most common reasons for rejection of the vaccination include being afraid of side effects of the vaccine, not believing the effectiveness of the vaccine and not considering the vaccine safe [18].…”
Section: Discussionsupporting
confidence: 72%
“…In addition to the questions about not having the influenza vaccination, some staff reported that their natural immunity is better and the vaccinations are manufactured for commercial benefits. The concern about influenza complications 16 The concern about spreading the disease to others 12/11.1 15/20. 5…”
Section: Resultsmentioning
confidence: 99%
“…Universal use of mask irrespective of vaccination status is effective in reducing nosocomial transmission of influenza, but may be difficult to implement [57, 58]. HCW vaccination, cohort nursing and antiviral prophylaxis for high risk patients during an outbreak reduce transmission and the deleterious consequences of influenza infection, including lower respiratory tract infections [46, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Brandt ve arkadaşları (14) 2011 yılında 1645 sağlık personeli üzerinde yaptık-ları çalışmada aşı yaptırmama nedenlerini ajuvanlardan korkma (%33.6), kendini riskli grupta hissetmeme (%33.4) olarak bildirmişlerdir. Giannattasio ve arkadaşları (13) ise 2015 yılın-da 2557 sağlık personeliyle yaptıkları çalışmada, aşılanmama sebeplerini, kendini riskli grupta hissetmeme (%32.6), aşının etkinliğinden şüphe duyma (%33.7) olarak sıralamışlardır.…”
Section: İrdelemeunclassified